Perceptions on conservation measures in mossy forest at Cameron Highlands - Rosli, Muhammad Rozaimie (2019)
Interest in climbing activities encourages many tourists to visit Cameron Highlands. In this area, there is a mossy forest which is very popular among climbers because of its unique and refreshing nature. This forest is covered with most moss because of the high altitude. However, the mossy forest is affected by irresponsible climbers. Hence, a perception survey is conducted to gather information on mossy forest conservation measures. This study uses Spearman's correlation analysis as a means to determine the relationship between perceptions of conservation measure for mossy forest in Cameron Highlands with particular socio-demographic of the respondents. Data were obtained using a closed questionnaire through the face-to-face interview. The questions asked includes the respondents’ perceptions on issues of waste disposal, behaviour such as trampling and touching the moss, and conservation measures in mossy forest. There were 119 respondents involved in this study, and the study found that gender, age, and education levels were related to the perceptions about mossy forest conservation measures. The approach in determining the perception on conservation measure of mossy forest in Cameron highlands can assist in providing additional information and guidance for decision-making processes related to conservation of the mossy forest in Cameron Highlands.